Stigma against health care providers caring for COVID-19 patients in Turkey - Abdulqadir J. Nashwan (11659453) (2022)
Health care providers (HCPs) worldwide have been a common target for stigmatization during widespread infections, such as COVID-19. The purpose of this study is to highlight the prevalence of stigmatization during the COVID-19 pandemic among HCPs in Turkey using the Stigma COVID-19 HCPs instrument (S19-HCPs). Descriptive design. The S19-HCPs is a self-administered, web-based survey (24 items) developed previously. The internal consistency of the S19-HCPs’ Turkish version was satisfactory (α = 0.79). Test-retest correlations were all statistically significant for the Turkish version of the instrument (ICC = 0.90, p0.01). Most study participants were 20–30 years old (77%); among the respondents, 66% had worked in a COVID-19-designated facility. Stigma against HCPs is highly prevalent in Turkey. The outcomes of this study revealed substantial levels of HCP stigmatization in Turkey irrespective of their motivation to work with COVID-19 patients. Education, media, and awareness campaigns might play a critical role in addressing global stigmatization issues. Other Information Published in: Cogent Public Health License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/27707571.2022.2110191